IMPLEMENTATION OF CORETAX IN GENERATING E-BUPOT UNIFICATION AT PT FEDERAL INTERNATIONAL FINANCE LAMPUNG BRANCH - Azzahro, Latifah; Niken Kusumawardani; Syafis, Kamadie Sumanda; Ratna Septiyanti (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2025)
This study aims to determine the use of Coretax application in making e-Bupot Unification at PT Federal International Finance (FIFGROUP) Lampung Branch. e-Bupot Unification is an electronic document used to report tax withholding and collection by tax withholders or collectors. The use of Coretax as an integrated taxation system is expected to simplify and speed up the company's tax administration process, especially in terms of Unification e-Bupot reporting. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the use of Coretax in making e-Bupot Unification has been running well and provides convenience for tax staff in terms of time efficiency, data management, and compliance with applicable tax provisions. However, there are still some obstacles such as technical glitches in the system and the need for increased training for users in order to maximize the use of the Coretax application. Keywords: Coretax, e-Bupot Unification, Tax Administration